Chile : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, and Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2004)
This paper highlights key findings of the Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, and Securities Regulation for Chile. The assessment reveals the Chilean banking system to be sound, resilient to shocks, and well supervised. Banks are well capitalized, profitable, internationally integrated, and have relatively low nonperforming loans. Stress tests indicate that they would absorb sizable macroeconomic shocks with only a moderate impact on their solvency. Although bank competition remains limited, it has increased significantly in recent years.